STUDI ANALISIS DAYA DUKUNG PONDASI TIANG PADA PEMBANGUNAN GEDUNG LP3M UNIVERSITAS KADIRI - Agata Iwan Candra; Anasrudin Yusuf; Amanda Rizky F (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
The foundation is a part of the building construction which is responsible for accepting and eradicating all the load from the building either live load or dead load from a land market building which is strong enough to support it . To determine the soil bearing capacity soil investigation needs to be done so that the building that are above the ground is not decreased (settlelment) is large enough, then the foundation must reach solid ground layer and the bearing capacity of the soil (bearing capacity) are permitted.   Strous foundation and bored pile used if the ground conditions in the bottom of the building does not have sufficient load bearing capacity to carry the load or if the hard soil that has a strong carrying capacity is located very deep from the ground surface. The purpose of this study is to calculate the carrying capacity of Strous Meyerhoff and Begemann on sondir results.